SASARAN DAN EVALUASI ANGGARAN: KETIDAKPASTIAN LINGKUNGAN DAN PENGALAMAN MANAJER SEBAGAI VARIABEL KONTINJENSI - Dr. Mohammad Nizarul Alim, M.Si., Ak. (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
Most of budgets studies have focused on budget participation. It was argument that level of participation in budgeting process is most important part of budgeting procedure. The activity could predict and reduce future uncertainty. The others components of budgeting like budget goal and budget evaluation lacked attention. This study aims to investigate the impact of budget goal difficulty and budget evaluation style on managerial performance and job satisfaction with contingency approach.  Level of difficulty would arise when environment uncertainty exist. It should need different style of budget evaluation. But, experience managers seem could anticipate it. Results support hypothesis that budget goal difficulty and budget evaluation style were contingent with manager experience and environment uncertainty